DIAGNOSIS OF MASTITIS IN ETAWA CROSSBREED GOATS - Usma Aulia; Rikamalia; Anna Zukiaturrahmah; Juliadi Ramadhan; Ario Ridho Gelagar (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Mastitis is a disease which occur as result of the infection in mammary gland. Mastitis in Etawa Crossbred goat is commonly found and caused economic loss. Subclinical mastitis causes decrease in milk production and milk quality. Subclinical mastitis is a type of mastitis which does not show clinical symptoms. The purpose of this study was to diagnose subclinical mastitis on Etawa Crossbred goat by using the IPB-1 test. This study was a descriptive research. Detection was done by taking milk samples on Etawa Crossbred goat purposively and was reacted with IPB-1 reagents which were circulated circularly for 15-20 seconds. The observation of the reaction results of milk and reagent were determined based on consistency changing with the coagulation period. In this case, blood tests were also carried out. The results showed that Etawa Crossbreed goats was detected with subclinical mastitis with a score of +2 using the IPB-1 test method. The results of blood tests showed that the goat had hyperchromic macrocytic anemia, leukocytosis and monocytosis. Based on the results of the anamnesis, physical examination, and laboratory results, the goat was found to have subclinical mastitis with a fausta prognosis. It is hoped that a thorough examination and the use of different methods can identify the cause of subclinical mastitis in PE goats and facilitate the treatment.